PENGARUH KOMISARIS INDEPENDEN, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP MANAJEMEN LABA - Winda Amelia; Erna Hernawati (Trunojoyo University of Madura, 2016)
This study is performed to examine the effect of commissioner independent, firm size and profitability to earnings management in services company sectors real estate, property and contruction building company listed on the Indonesia Stock Exchange in the period 2009 until 2013. The population of this study is a number of 25 companies services sectors real estate, property and contruction building company listed on the Indonesia Stock Exchange over period 2009-2013 publication. The data is obtained based on the corporate finance reporting statement are publication in the Indonesia Stock Exchange (BEI). The sampel in this study using purposive sampling and obtained a sampel of 13 companies services from 25 companies those are classified insectors real estate, property and contruction building in Indonesia Stock Exchange (BEI) in the period 2009 to 2013. The analysis technique used in this research is multiple linier regression analysis and hypothesis testing using the F test and t test. The research result showed that commissioners independent and profitability is had no significant effect on earning management and variabel firm size is had a significant effect on earning management. and the result on simultan test (F) showed the independent variables, commissioners independent.